Antibiofilm activity of nanoemulsions of Cymbopogon flexuosus against rapidly growing mycobacteria. (December 2017) - Rossi, Grazielle Guidolin; Guterres, Kevim Bordignon; Bonez, Pauline Cordenonsi; da Silva Gundel, Samanta; Aggertt, Vanessa Albertina; Siqueira, Fallon Santos; Ourique, Aline Ferreira; Wagnerd, Roger; Klein, Bruna; Santos, Roberto Christ Vianna; de Campos, Marli Matiko Anraku
Abstract: Rapidly growing mycobacteria (RGM) are opportunistic microorganisms that can cause both local and disseminated infections. When in biofilm, these pathogens become highly resistant to antimicrobials used in clinical practice. Composed abundantly of polymeric substances, biofilms delay the diffusion of antimicrobials, preventing the drug from penetrating the deeper layers and having an effective action. Therefore, the search for new and alternative therapeutic options has become of fundamental importance. Natural products fall into these options, especially essential oils. However, these oils present problems, such as low miscibility in water (which decreases its bioavailability) and degradation by light and temperature. Thus, the objective of this work was to explore the action of free essential oil and nanoemulsions of Cymbopogon flexuosus on strains of RGM, in planktonic and sessile forms. In this work, standard strains of Mycobacterium fortuitum (ATCC 6841), Mycobacterium massiliense (ATCC 48898) and Mycobacterium abscessus (ATCC 19977) were used. The susceptibility of the microorganisms in planktonic form was obtained by conventional microdilution techniques and by cell viability curve. The analysis of the antibiofilm activity was performed by a semi-quantitative macrotechnique. The nanoemulsion exhibited significant antimicrobial activity, with minimum inhibitory concentration values lower than those presented by the free essential oil, against strains in the planktonic state. However, both were efficient in destroying the already formed biofilm, whereas only the free oil inhibited the formation of mycobacterial biofilm. This study demonstrated the therapeutic potential of C. flexuosus essential oil, especially in its nanostructured form, which can be demonstrated against infections caused by rapidly growing mycobacteria. Highlights: This study evaluated the EO activity of lemongrass against RGM. Free EO was able to inhibit RGM biofilm formation. LGNE was effective against RGM biofilm. LGNE was presented as a promising antimicrobial agent against mycobacteriosis.